Screening non-MAPT genes of the Chr17q21 H1 haplotype in Parkinson's disease. (September 2020) - Soto-Beasley, Alexandra I.; Walton, Ronald L.; Valentino, Rebecca R.; Hook, Paul W.; Labbé, Catherine; Heckman, Michael G.; Johnson, Patrick W.; Goff, Loyal A.; Uitti, Ryan J.; McLean, Pamela J.; Springer, Wolfdieter; McCallion, Andrew S.; et al.
Abstract: Introduction: The microtubule-associated protein tau ( MAPT ) gene is considered a strong genetic risk factor for Parkinson's disease (PD) in Caucasians. MAPT is located within an inversion region of high linkage disequilibrium designated as H1 and H2 haplotype, and contains eight other genes which have been implicated in neurodegeneration. The aim of the current study was to identify common coding variants in strong linkage disequilibrium (LD) within the associated loci on chr17q21 harboring MAPT . Methods: Sanger sequencing of coding exons in 90 Caucasian late-onset PD (LOPD) patients was performed. Specific gene sequencing for LRRC37A, LRRC37A2, ARL17A and ARL17B was not possible given the high homology, presence of pseudogenes and copy number variants that are in the region, and therefore four genes ( NSF, KANSL1, SPPL2C, and CRHR1 ) were included in the analysis. Coding variants from these four genes that did not perfectly tag (r 2  = 1) the MAPT H1/H2 haplotype were genotyped in an independent replication series of Caucasian PD cases (N = 851) and controls (N = 730). Results: In the 90 LOPD cases we identified 30 coding variants. Eleven non-synonymous variants tagged the MAPT H1/H2 haplotype, including two SPPL2C variants (rs12185233 and rs12373123) that had high pathogenic combined annotation dependent depletion (CADD) scores of >20. In the replication series, the non-synonymous KANSL1 rs17585974 variant was in very strong LD with MAPT H1/H2 and had a high CADD score of 24.7. Conclusion: We have identified several non-synonymous variants across neighboring genes of MAPT that may warrant further genetic and functional investigation within the biological etiology of PD. Highlights: MAPT H1 is a consistent Parkinson's disease association locus on chr17q21. Chr17q21H1 extended haplotype is a complex genetic region of inversion. Other genes/variants in complete linkage disequilibrium may be responsible. Potentially damaging variants in KANSL1, NSF and SPPL2C .